An Innovative Approach for Treating Chronic Vaginitis Based on AI-Driven Drug Repurposing - Daungsupawong, Hinpetch; Wiwanitkit, Viroj (Khazanah Informatika : Jurnal Ilmu Komputer dan Informatika, 2024)
This study evaluates the effectiveness of ChatGPT, an AI language model, in assisting healthcare practitioners in selecting drugs for treating chronic vaginitis, which is still an important medical problem. A panel of experts assessed ChatGPT’s recommendations for ten fictional clinical scenarios related to this condition. The study aims to determine if ChatGPT can provide accurate and relevant guidance on pharmaceutical options for managing chronic vaginitis.The authors use the set of question as input to ChatGPT system to derive the output then the output was further validated by expert panel. The results show that ChatGPT consistently offers valuable suggestions for potential drug repurposing, supported by scientific evidence. Despite limitations, such as the need for more clinical data and the inability to modify treatment, ChatGPT shows promise as a tool for drug repurposing in the treatment of chronic vaginitis. The present study is a novel approach in applying the AI based technique for drug repurposing in clinical medicine. Future research should focus on refining the model’s capabilities, incorporating more comprehensive clinical data, and enabling customization of treatment plans to enhance its effectiveness in assisting healthcare practitioners.By addressing these issues, ChatGPT could become a valuable resource for managing chronic vaginitis in females.